Cycloaddition of N-sulfonyl and N-sulfamoyl azides with alkynes in aqueous media for the selective synthesis of 1, 2, 3-triazoles. Issue 2 (6th January 2022) - Prasanth, Thumpati; Chakraborti, Gargi; Mandal, Tirtha; Ravichandiran, Velayutham; Dash, Jyotirmayee
Abstract : The cycloaddition of N -sulfonyl and sulfamoylazides with terminal alkynes using a prolinamide ligand selectively provides 1, 2, 3-triazoles in aqueous media in the presence of CuI. Abstract : The cycloaddition of N -sulfonyl and N -sulfamoyl azides with terminal alkynes generally produces amide derivatives via ketenimine intermediates. We herein delineate a Cu(i ) catalyzed method using a prolinamide ligand that selectively generates N -sulfonyl and sulfamoyltriazoles in aqueous media by inhibiting the cleavage of the N 1 –N 2 bond of 5-cuprated triazole intermediates. The present method is mild and tolerant to air, moisture and a wide range of functional groups, thereby providing easy access to a variety of triazole products.